As impressões, as manifestações e as repercussões do caso Sacco e Vanzetti na imprensa: um estudo centrado no(s) cenário(s) brasileiro(s) - Soares, Eduardo da Silva (2020)
This investigation was in accordance with the studies of the Graduate Program in History at the Federal University of Santa Maria, whose investigation was centered on the Culture, Migration and Work Research Line. Based on the debates held throughout the course, research was concentrated in the 1920s and in the context of workers. Many of them became involved with anarchism and suffered for the choice. Thousands decided to migrate in search of better jobs, housing, and security. Countless people paid a high price for the combination: workers, activists, and migrants. In this context, two stood out in the international press: Nicola Sacco and Bartolomeo Vanzetti. Two Italians, workers and migrants in the United States of America faced Red Scare and became social martyrs. In this way, Sacco and Vanzetti were studied through the press, and more precisely, according to their representations. In this sense, they were problematized as impressions, as manifestations and as repercussions of the Sacco and Vanzetti case in the Brazilian press. For this, the newspapers of great circulation were studied, as well as the libertarian and Italian-Brazilian newspapers. It is believed that the publications referring to the protests, strategies and practices of the pro Sacco and Vanzetti groups help to unveil the repercussions of this case in the Brazilian press. The thesis defended here is: the presses approve the repercussion of the Sacco and Vanzetti case to create images of the good worker - orderly; the social martyr - and, in the libertarian press, the anarchist martyr. To support the thesis, the press is the active subject of the process. Therefore, the first chapter studied the newspapers and the concepts that guided the construction of the thesis. And, based on the understanding that newspapers were resources that propagated the speeches that formed public opinion, it is proposed now, which presents the case of Sacco and Vanzetti in their American context. To understand how they occurred and how it was possible to have such a primordial case to think about the speeches propagated in the presses of Brazil, because the writers, mainly the militants, whenever possible, compared as conjunctures and as conditions of the workers of these two countries. Finally, the synthesis was presented from the reflection on the construction and the elements included for a subject to be considered a martyr, which involved thinking about the disputes for the right to speak about Sacco and Vanzetti: in that context, who could and who could divert the about that “famous case”?